Based on Plasma Metabonomics and Network Pharmacology Exploring the Therapeutic Mechanism of Gynura procumbens on Type 2 Diabetes - Guo, Wenjing; Ouyang, Hui; Liu, Mi; Wu, Jiahui; He, Xiao; Yang, Shilin; He, Mingzhen; Feng, Yulin (Frontiers in Pharmacology, 2021)
Gynura procumbens(GP) is a perennial herbal medicine and food homologous plant, it has been reported that it has a good hypoglycemic effect, but so far, its active components and mechanism are not clear. We intended to confirm the effects of GP on type 2 diabetic (T2DM) from several aspects. In this study, we used UPLC/Q-TOF MS to analyze the metabolic patterns, which included plasma of clinical subjects and db/db mice to screen serum metabolic markers and metabolic pathways and using the network pharmacology to speculate the target of GP in the treatment of T2DM. The endogenous metabolite in plasma concluded two common pathways, which included glycerol phosphate metabolism and retinol metabolism were detected in the plasma samples of the two type groups. Finally, the western blot was used to verify the expression of relevant proteins in PI3K/AKT and AGE-RAGE signal pathways. The protein expressions of AKT, eNOS, iNS and MAPK were activated and significantly up-regulated, while Caspase8 and Caspase3 were significantly down-regulated. The above results indicate GP could alleviate the insulin resistance by regulating the biometabolic markers and the key proteins in the signal pathway to treat T2DM.